Mahdoton kilpajuoksu? Oikeus viestinnän kehityksen mahdollistajana - Neuvonen, Riku (Lakimies, 2023)
Impossible race? Law as an enabler of the technological development of communication In the history of freedom of speech, the law has been seen as an obstacle to economic and commercial innovations. However, technological development is a key part of the history of freedom of speech. Freedom of speech has been synonymous with freedom of the press, which as a concept refers to specific communication technology. Internet regulation is based on the exemption of liability for certain internet companies. This has created a new public space and new business models. Now this activity is being reined in again through law. The central question posed by the article is how law and communication technology interact and how the law can act as an enabler.